PENGARUH INDEPENDENSI, PENGALAMAN, ETIKA, DUE PROFESSIONAL CARE DAN MOTIVASI AUDITOR TERHADAP KUALITAS AUDIT - Harry Budiantoro; Corry Muslimah Ogan; Kanaya Lapae; Hestin Agus Tantri Ningsih; Adinda Primadini (Eqien - Jurnal Ekonomi dan Bisnis, 2022)
The goal of this study is to see how concurrent and partial independent, experience, ethics, professional prudence, and motivation affect audit quality from an Islamic standpoint. This study relied on primary data. Data for this study were gathered through questionnaires distributed to study participants. The data in this study was analyzed using multiple linear regression. The findings of this study suggest that audit quality is positively influenced by independence, experience, ethics, due professional care, and auditor motivation. At a Public Accounting Firm (KAP) in the North Jakarta Region, independence, experience, ethics, due professional care, and motivation all have a positive and significant effect on audit quality.